2015
DOI: 10.7314/apjcp.2015.16.17.7981
|View full text |Cite
|
Sign up to set email alerts
|

Having Private Cancer Insurance in Korea: Gender Differences

Abstract: Background: As coverage of public insurance is not sufficient to cover diagnosis or treatment of cancer, having private health insurance is important to prepare for unexpected expenses of cancer. The purpose of this study was to assess factors associated with having private cancer insurance, considering gender among the sociodemographic factors and health behavior. Materials and Methods: We used data from the 2011 Korea Health Panel, which included 10,871 participants aged 20 years and older. Socio-demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A meta-analytic review concluded that individuals perceiving themselves to be at a greater risk of developing breast cancer were more likely to undertake cancer screening [ 27 ]. Similarly, under the country’s universal health care plan, a Korean survey found that perceived cancer risk possibility was significantly associated with having private cancer insurance only amongst females, and that females with private cancer insurance were more likely to follow precautionary healthy behavior than males [ 28 ]. The perceived cancer risk within the Korean population was also associated with their participation in cancer screening [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analytic review concluded that individuals perceiving themselves to be at a greater risk of developing breast cancer were more likely to undertake cancer screening [ 27 ]. Similarly, under the country’s universal health care plan, a Korean survey found that perceived cancer risk possibility was significantly associated with having private cancer insurance only amongst females, and that females with private cancer insurance were more likely to follow precautionary healthy behavior than males [ 28 ]. The perceived cancer risk within the Korean population was also associated with their participation in cancer screening [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, national health insurance covers Pca treatments, except stereotactic body radiation and robotic surgery. It covered 22.4% of all cancer patients in 2011; private insurance covered Pca treatments, including stereotactic body radiation and robotic surgery 34. Our previous study reported that radiation therapy for Pca, including stereotactic body radiation, had continuously increased from 2005 to 2014.…”
Section: Discussionmentioning
confidence: 99%